Reports on boys', youth's and men's health in Canadian newspapers: Now what? - Margareth Santos Zanchetta; Aaron Andrew Byam; Donna Solomon; Katayoon Jalili; Carlos Haag; Silvia Tallarico (Tabriz University of Medical Sciences, 2017)
Background: This media content analysis explored the Canadian newspapers reporting on men's health, and their contribution to public understanding of the social determinants of men's health and lifestyles. Methods: A media content analysis of 44 news articles on boys', youth's and men's health,published from 2010 to 2014 by three national newspapers (The Globe and Mail, National Post,and Metro News). Results: Data indicated that the predominant discourse consists of informative and awareness messages, mostly about men's prostate and sexual health. Very little health news content referred to working conditions, education and income, all of which are significant social determinants of health (SDH). This may reflect the current state of health research, which does not adequately incorporate the effects of these determinants. It may also indicate a reproduction of dominant health knowledge and understanding of masculinity. Little content was found on policy solutions to other publicized health issues, such as limited access to health services or inter-sectoral collaborations; this reflects a lack of government action and a lack of citizen engagement toward the creation of a concerted men's health policy. Conclusion: Despite the acknowledged importance of the media in promoting access to health information and indirectly contributing to improve the general public's level of health literacy, it is also necessary to remember that there must be a greater attention to the structural constraints imposed by socioeconomic inequalities. Future studies should explore media discourses about men's unequal access to health care services and citizens' awareness of ways to overcome those inequalities shortcomings.